Nuevos estudios del esqueleto del sitio Cerro Yanquenao (Colhue Huapi, Chubut) : Veintiocho años después - García Guraieb, Solana (2009)
The purpose of this communication is to present a reassessment of bioarchaeological data of the skeletal remains from the archaeological site Cerro Yanquenao (Chubut, Argentina). The new studies indicate that this individual is a male, aged between 40-50 years at the time of death. The cranium shows artificial deformation of tabular erect type, planolambdic variety. A fragment of rib analyzed by AMS indicated an age of 1.151 ± 59 years BP. δC13 (-18.5 ‰) and δN15 (11.5 ‰) values are within the range expected for terrestrial diets in continental Patagonia. Also, several bony lesions were identified. The most conspicuous ones were found in the upper and lower limbs and the skull and might be compatible with a variety of Treponematosis. These results are discussed in relation to the current approaches and bioarchaeological information known for the region.